2014
DOI: 10.3102/0162373714534521
|View full text |Cite
|
Sign up to set email alerts
|

High-Stakes Choice

Abstract: This article considers the impact of a high-stakes testing and reporting requirement on students using publicly funded vouchers to attend private schools. We describe how such a policy was implemented during the course of a previously authorized multi-year evaluation of the Milwaukee Parental Choice Program, which provided us with data on voucher students before and after the reform, as well as on public school students who received no new policy treatment. Our results indicate substantial growth for voucher s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…1 The law also required a new evaluation, conducted by independent researchers, to report on program outcomes. The data for this paper are drawn from that official evaluation of the MPCP, which occurred between 2006 and 2011 (Witte et al, 2008(Witte et al, , 2014.…”
Section: Data and Program Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…1 The law also required a new evaluation, conducted by independent researchers, to report on program outcomes. The data for this paper are drawn from that official evaluation of the MPCP, which occurred between 2006 and 2011 (Witte et al, 2008(Witte et al, , 2014.…”
Section: Data and Program Backgroundmentioning
confidence: 99%
“…However, while the original Witte et al (2008) study indicated that more than 70 percent of MPCP students had at some point been in the public sector (see also Cowen et al, 2012), such transfers occurred prior to the beginning of data collection in 2006-07, and we observe in this paper only the panelists who were already in the voucher sector. Fleming et al (2014) consider regression-adjusted differences between voucher students and the panel of public school students, but these were based on otherwise "similarly situated" students on the basis of 2006 test scores, racial demographics and, critically for our purposes here, between public/private school students within the same neighborhoods (this study found that religious behavior was among the key predictors of voucher take-up within the same neighborhoods).…”
Section: Neighborhood Transfer and Voucher Exitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Berends (2014) states that private school voucher programs are growing in urban areas, yet their effects on urban education systems are inconsistent. For example, in Milwaukee vouchers were shown to have a positive impact on high school graduation rates, but little to no significant impact on student test scores (Cowen et al, 2013; Witte et al, 2014). More recent studies in New Orleans and Washington, D.C., find that vouchers actually have a negative impact on student test scores (Dynarski, 2016; Dynarski et al, 2017; Mills & Wolf, 2017).…”
mentioning
confidence: 99%